Phylogeny and evolutionary biology of Platycheirus (Diptera: Syrphidae) - Jaf, Aram (2019)
The goal of this project is to address the phylogeny and evolutionary biology for one of the most diverse and species-rich genera of flower flies (Diptera: Syrphidae), Platycheirus LePeletier & Serville. Although studied taxonomically for a long time, the phylogenetic relationships of its species groups, subgroups and species are not well understood; this is especially the case for large genera of hoverflies.